2012
DOI: 10.1177/1098300712459080
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Reading Skill and Problem Behavior in Elementary School

Abstract: The purpose of this study was to explore interactions among reading skill, problem behavior, and gender across elementary school. A 6-year, longitudinal study (N = 473) was conducted to identify the relations among these variables and change in relations from kindergarten to Grade 5. Students’ reading skills and levels of problem behavior were examined. Mixed model analyses of variance indicated no differences in reading skill by gender, but a significant gender interaction for problem behavior. Correlations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 51 publications
1
21
3
Order By: Relevance
“…The study findings don't also endorse those of McIntosh, Reinke, Kelm, and Sadler (2013) and DiPrete and Jennings (2012) who indicated that reading difficulties are more common in boys than in girls, and Girls differ from boys in their social functioning since, due to academic gender gap, they could demonstrate stronger social and behavioral skills than those of young boys.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…The study findings don't also endorse those of McIntosh, Reinke, Kelm, and Sadler (2013) and DiPrete and Jennings (2012) who indicated that reading difficulties are more common in boys than in girls, and Girls differ from boys in their social functioning since, due to academic gender gap, they could demonstrate stronger social and behavioral skills than those of young boys.…”
Section: Discussioncontrasting
confidence: 48%
“…However, ascertainment bias could take place as boys with reading problems are more likely than girls to show disruption resultant from their reading problem (Quinn & Wagner, 2015). Reading difficulties and behavior problems are more common in boys than in girls (McIntosh, Reinke, Kelm, & Sadler, 2013). Girls differ from boys in their social functioning (DiPrete & Jennings, 2012).…”
Section: Dyslexia and Gender Gap In Reading Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Children who read proficiently by Grade 3 are more likely to graduate from high school (Hernandez, 2012). Conversely, poor reading ability has been linked to behavioral difficulties at school (Halonen, Aunola, Ahonen, & Nurmi, 2006; McIntosh, Reinke, Kelm, & Sadler, 2013). Prosocial skills are also key to school readiness, and individuals who show greater prosocial skills at school entry are more likely to graduate from high school, complete college, and obtain full and stable employment in young adulthood (Jones, Greenberg, & Crowley, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Being a proficient reader and being able to extract meaning from text is crucial for academic achievement in most theoretical school subjects (García-Madruga, Vila, Gómez-Veiga, Duque, & Elosúa, 2014; National Assessment Governing Board, 2013). Thus, together, social functioning and reading proficiency are important for a child's wellbeing and academic performance (McIntosh, Reinke, Kelm, & Sadler, 2012;OECD, 2015). Mastering the skills of social functioning and reading will not only allow children to develop social and academic competence in school Stewart, Benner, Martella, & Marchand-Martella, 2007), but also prepare them for successful participation in society and the workplace (Heckman, 2000(Heckman, , 2011 NOU, 2015:8).…”
mentioning
confidence: 99%